Penglibatan pelajar universiti dalam membangunkan kemahiran pemikiran kreatif melalui aktiviti kerja berpasukan - Abdul Hamid, Roshayati; Ismail, Md Daud (Universiti Utara Malaysia, 2020)
Creative thinking is a compulsory added value within students of Malaysian Higher Education Institutions (MHEIs) in contributing to the innovative national development. The development of an individual who has creative thinking skills must begin as early as pre-school education and continue to be practised at the tertiary level. Almost all MHEIs have focused on the development of creative thinking skill among students in the teaching and learning structure through teamwork. Nonetheless, studies that specifically test the influence of teamwork composition, namely proactive personality and emotional intelligence of team members on the development of students’ creative thinking are rather scarce. Previous studies found that not all teamwork is able to produce great outcome due to the fact that there is no chemistry among team members. Thus, great teams not only have to choose the best members but they also need to have a composition of members that can collectively develop high level of creative thinking skills . Every team member must take part in the creative process that facilitates the development of creative thinking skills. This process encompasses several steps of activities namely identifying problems, finding information, coding and generating ideas and alternatives in problem-solving. The purpose of this study is to test the relationship between individual characteristics in team composition and creative process as well as to the extent of which the creative process can develop students’ creative thinking skills in teamwork. The study sample comprises 250 students from six Malaysian HEIs (40- 50 questionnaires per HEI) with the questionnaires distributed online. The data from 242 respondents were tested using SPSS software (version 22). The findings of the study reveal that there was a positive and significant relationship between the proactive personality and emotional intelligence of the students and the students’ involvement in the creativity process. There was also a positive and significant relationship between the creativity process and the development of creative thinking skills.